Pendampingan Penyusunan Laporan Laba Rugi Usaha Mikro Kecil Dan Menengah (UMKM) Gula Aren Curup - Hidayah, Nenden Restu; Susena, Karona Cahya; Astuty, Kamelia; Amandari, Sevti; Sari, Yulita (Jurnal Dehasen Mengabdi, 2023)
The business that is currently in our spotlight is the Gula Aren Curup MSME business. These MSME businesses still prepare financial reports in a simple manner so that owners find it difficult to know the profits earned in detail. Therefore, we provide assistance in completing the profit and loss report for Micro, Small and Medium Enterprises (MSMEs) of Gula Aren Curup. In this problem, we aim to help prepare financial reports properly, especially in the income statement manually and using the cash book application which in the future will make it easier for owners to calculate the profit earned.